Diagnostic and Prognostic Value of Circulating miR-221 for Extranodal Natural Killer/T-Cell Lymphoma. Issue 5 (21st May 2013) - Guo, Hong-Qiang; Huang, Guo-Liang; Guo, Cheng-Cheng; Pu, Xing-Xiang; Lin, Tong-Yu
Abstract : Extra-nodal natural killer T-Cell (NK/T-cell) lymphoma is a progressive cancer with poor prognosis due to the lack of disease specific treatment. To develop specific therapeutic strategies, it is essential to identify tumor markers. Recent studies show that circulating microRNA (miRNA) may serve as diagnostic and/or prognostic markers for some diseases. To explore miRNAs as potential diagnostic and/or prognostic markers of NK/T-cell lymphoma, in our study, we compared circulating miR-221 levels in 79 patients and 37 normal subjects by real-time PCR amplification directly from plasma samples, and correlated patient's miR-221 levels with their clinic features and treatment outcomes. We observed a significant difference between the patient and control groups ( p =0.038), and a correlation of plasma miR-221 level in patient with sex, as well as a reverse correlation with performance status and the overall survival after treatment. Univariate and multivariate analyses further revealed that plasma miR-221 level, age, B symptoms, LDH level and complete response after primary treatment all present prognostic values when judged by overall survival (OS). Together, our results show that it is feasible to perform direct amplification of plasma miRNAs without total RNA extraction, and plasma miR-221 may be a diagnostic and prognostic marker for NK/T-cell lymphoma.